Treatment of chronic akinetic mutism with atomoxetine: subtraction analysis of brain f-18 fluorodeoxyglucose positron emission tomographic images before and after medication: a case report - Kim, Yong Wook; Shin, Ji-Cheol; An, Young-Sil (Clinical neuropharmacology, 2010)
Akinetic mutism is a rare, complex neuropathologic disorder. The pharmaceutical treatment of akinetic mutism typically includes dopaminergic agents, but the resulting therapeutic effects are often unsatisfactory, and it remains unclear whether late treatment using these medications is effective. We present a case study of a 53-year-old male patient who developed akinetic mutism for a period of 7 months after a subarachnoid hemorrhage. The hemorrhage was caused by a ruptured aneurysm in the right anterior communicating artery, followed by a secondary infarction in the territory of the right anterior cerebral artery. Baseline brain F-18 fluorodeoxyglucose positron emission tomographic images revealed decreased glucose metabolism in both frontal lobes. Treatment with atomoxetine, a selective norepinephrine reuptake inhibitor, for a period of 8 weeks led to a clinically significant improvement in the patient's cognitive function and activities of daily living. A subtraction brain positron emission tomographic analysis after atomoxetine medication revealed increased cerebral glucose metabolism in both the premotor and visual association cortices. Thus, we suggest that atomoxetine can be a useful therapeutic option in the treatment of chronic akinetic mutism.